Transcriptomic Analysis Provides New Insights into Oocyte Growth and Maturation in Greater Amberjack (Seriola dumerili) - Jiahui Yang; Xiaoying Ru; Yang Huang; Jinhui Wu; Tonglin Yang; Peipei Chen; Jin Li; Kunfeng Zhu; Chunhua Zhu (Animals)
The greater amberjack (Seriola dumerili) is an emerging marine fish that is increasingly favored in aquaculture. Currently, there are few studies on the development and regulation of greater amberjack ovaries. In this study, the ovary transcriptome profiles of greater amberjack at three different stages (stage II, III, and IV) were performed, and identified the genes and pathways that may play significant roles in the processes of follicle growth and maturation. A total of 6597, and 1061 differentially expressed genes (DEGs) were detected in FII vs. FIII, FIII vs. FIV, and FII vs. FIV stages, respectively. GO and KEGG enrichment analyses revealed that these DEGS are primarily involved in steroid hormone biosynthesis (e.g., cyp11a1, cyp17a1, cyp19a1a, hsd3b1, esr1), lipid metabolism (e.g., plpp3, lpl, pld1, and fabp10a), and meiotic arrest and resumption (e.g., pgr, arb, ccnd2, adcy2, adcy9, myl9, calm1). Additionally, several signaling pathways involved in ovarian development have been identified, including the PI3K-Akt, Wnt, TGF-beta, GnRH, and immune-related signaling pathways. qPCR results of nine representative genes related to steroid hormone synthesis and cell growth verified the reliability of the generated RNA-seq data. This research contributes to our comprehension of the molecular processes underlying ovarian growth and maturation in marine fishes and provides a theoretical basis for the investigation of functional genes associated with oogenesis in greater amberjack.